The electron diffusion coefficient tensor by using the real geometry of the Earth’s magnetic field in ionospheric plasma - Yesil, A.; Sanac, G.; Unal, I. (My University, 2013)
In this study, the electron diffusion coefficients are calculated as depending on latitude, local time and seasonal in the ionospheric plasma by using the real geometry of Earth’s magnetic field for north hemisphere. It is observed that if the earth’s magnetic field is taken into account, the medium is anisotropic in ionospheric plasma. Due to this, the electron diffusion coefficients have tensorial form in the ionospheric plasma. As general, there is a harmony between change of the electron diffusion coefficient and the change of the electron density with local time in the ionospheric plasma

Bu çalışmada, dünyanın gerçek manyetik alan geometrisi kullanılarak kuzey yarım küre için iyonosferik plazmada elektron difüzyon katsayıları yüksekliğe, yerel zamana ve mevsime bağlı olarak hesaplandı. Eğer dünyanın manyetik alanı hesaba katılırsa iyonosferik plazmada ortam anizotropik olur. Bundan dolayı iyonosferik plazmada elektron difüzyon katsayısı tensörel bir forma sahiptir. Genel olarak, elektron difüzyon katsayısının yerel zamanla değişimi ve elektron yoğunluğun yerel zamanla değişimi arasında bir uyum vardır
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Ionosphere; Diffusion; Ionospheric plasma; İyonosfer; Difüzyon; İyonosferik plazma